Synthesis and Spectral Investigation of Some New Crown Ether Ligands - Hayvali, Zeliha (Asian Journal of Chemistry, 2010)
The new crown ether ligands (5-6) were synthesized by condensation of 4' -formyl-5' -hydroxybenzo-15-crown-5 (4) with 2- chloroaniline and 3-bromoaniline. The structure of these compounds have been elucidated on the basis of elemental analyses, IR, 1H, 13C NMR, and UV-Vis spectroscopic techniques. The UV-V is spectra of the ligands (5-6) were studied in polar and non-polar solvents, as well as in acidic and basic media. The results indicate that the tautomeric equilibria (phenol-imine O—H·· N and keto-amine O... H—N forms) are present only in the EtOH solution. But in other solvents (DMSO, CHCI3, n-hexane), acidic and basic media only the phenol-imino form is dominant.